(untitled) (Research, Society and Development, 2021)
Objectives: To evaluate the insertion of epicutaneous catheters by nursing professionals and its risks and complications. Methods: Integrative literature review, carried out in the BVS and PubMed data libraries, using the LILACS, MEDLINE and BDENF databases, in order to search for articles available in Portuguese, English and Spanish, which were published between the period of January of 2015 and June 2021. Results: 160 articles were found in the literature search, including 9 articles in the final sample. The use of the Peripherally Inserted Central Catheter (PICC) is widely used in premature newborns, due to its immaturity and difficulty in maintaining the good functionality of vital organs. During the insertion of the PICC, some professionals administer mild sedatives or analgesics, but a study has shown that non-pharmacological treatment for pain relief is also very effective and sweetened solutions or breast milk are offered. Final Considerations: Given the above, we can note that the PICC catheter is the best option for newborns admitted to the Neonatal ICU who need continuous infusion therapy, antibiotic therapy and parenteral nutrition.